2018
DOI: 10.5194/nhess-18-1891-2018
|View full text |Cite
|
Sign up to set email alerts
|

Determining the drivers for snow gliding

Abstract: Abstract. Snow gliding is a key factor for snow-glide avalanche formation and soil erosion. This study considers atmospheric and snow variables, vegetation characteristics, and soil properties and determines their relevance for snow gliding at a test site (Wildkogel, Upper Pinzgau, Austria) during winter 2014/2015. The time-dependent data were collected at a high temporal resolution. In addition to conventional sensors, a “snow melt analyzer” was used. The analysis shows that the soil temperature 10 cm below t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…For example, in Pista Nera the VLWC in the snow was significantly higher for gliding than for non-gliding periods when considering the whole dataset or cold periods. This was also found by Fromm et al (2018) and Ceaglio et al (2017). Instead, in Sant'Anna there was no difference in the VLWC of snow during cold periods; a little significant difference was found in warm periods, but the VLWC of snow was higher in non-gliding than in gliding periods, revealing how other predisposing factors could contribute to the snow gliding process.…”
Section: Gliding Vs Non-gliding Periodsmentioning
confidence: 55%
See 3 more Smart Citations
“…For example, in Pista Nera the VLWC in the snow was significantly higher for gliding than for non-gliding periods when considering the whole dataset or cold periods. This was also found by Fromm et al (2018) and Ceaglio et al (2017). Instead, in Sant'Anna there was no difference in the VLWC of snow during cold periods; a little significant difference was found in warm periods, but the VLWC of snow was higher in non-gliding than in gliding periods, revealing how other predisposing factors could contribute to the snow gliding process.…”
Section: Gliding Vs Non-gliding Periodsmentioning
confidence: 55%
“…As WCR probes were mainly designed to measure volumetric liquid water content in soils, we were able to transform the values recorded by the instrument place in the basal snowpack layer following the corrections found by Godio et al (2018) during an experimental campaign carried out at the vicinity of the manual measuring site of Sant'Anna.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent studies by Ceaglio et al (2017) and Fromm et al (2018) underline the importance of soil moisture as a driving factor for snow gliding. In particular, Ceaglio et al (2017) found a strong relation between glide snow rate and moisture at the snow-soil interface for cold temperature events, with a possible contribution also of soil liquefaction, while Fromm et al (2018) found that soil moisture and temperature had a significant 15 influence on snow gliding in both warm and cold periods.…”
Section: Introductionmentioning
confidence: 99%